1982
DOI: 10.1542/peds.70.6.987
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Treatment of Hyperactive Children: Effects on the Hypothalamic-Pituitary-Somatomedin Axis

Abstract: To further define the influence of methylphenidate on the growth hormone-somatomedin axis and prolactin secretion, serum growth hormone and prolactin concentrations were assessed over 24 hours and in response to provocative stimuli. The nine hyperactive subjects were all studied during methylphenidate therapy and after drug discontinuation. Diurnal patterns of growth hormone and prolactin concentrations were assessed using an ambulatory, continuous blood withdrawal procedure to ensure that activity, caloric in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Direct effects of GH on cartilage are also known, however IGF-1 levels largely reflect the adequacy of GH production. Somatomedin C levels, examined in three studies, were not altered in patients chronically treated with stimulants (Bereket et al, 2005;Schultz et al, 1982;Toren et al, 1997). Kilgore et al (1979) also found that pemoline, methylphenidate, and methamphetamine can inhibit, in vitro, the sulphate uptake by cartilage, thus suggesting the change on cartilage metabolism as a possible mechanism of growth retardation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Direct effects of GH on cartilage are also known, however IGF-1 levels largely reflect the adequacy of GH production. Somatomedin C levels, examined in three studies, were not altered in patients chronically treated with stimulants (Bereket et al, 2005;Schultz et al, 1982;Toren et al, 1997). Kilgore et al (1979) also found that pemoline, methylphenidate, and methamphetamine can inhibit, in vitro, the sulphate uptake by cartilage, thus suggesting the change on cartilage metabolism as a possible mechanism of growth retardation.…”
Section: Discussionmentioning
confidence: 95%
“…Direct effects of GH on cartilage are also known, however IGF-1 levels largely reflect the adequacy of GH production. Somatomedin C levels, examined in three studies, were not altered in patients chronically treated with stimulants (Bereket et al, 2005; Schultz et al, 1982; Toren et al, 1997).…”
Section: Discussionmentioning
confidence: 98%